Automated synthesis of controlled cable-stayed footbridges with S-shaped deck. (November 2020) - Ferreira, Fernando; Simões, Luís
Highlights: A methodology is presented to find optimum solutions for a S-shaped cable-stayed bridges The lock-in instability sensitivity analysis with non-linear dampers equations are provided Two structural solutions are sought using passive and semi-active TMDs to control the bridge response Passive and semi-active solutions have different optimum geometries and sections Semi-active devices turn the solution more efficient given the highly coupled vibration modes. Abstract: Curved cable-stayed bridges (CSB) have been increasingly used in the past years. There are currently 42 operational CSB registered in the Structurae database, 37 of which have been built in the last two decades. The minimum cost design of curved S-Shaped pedestrian CSB with external pylons satisfying the static and dynamic code requirements (Eurocodes and Setra guidelines in this work) are found by using an optimization algorithm with polynomial convergence time. Dampers cannot be located at the pylon-deck connection because it does not exists, the structure being controlled by passive and semi-active tuned mass dampers. The sensitivity analysis considers the non-linear dynamic behaviour of the semi-active device. Two optimal solutions are sought using semi-active (S1) and passive (S2) dampers. The results show that both solutions have different geometries and cross sections. The pylon height is markedly higher for structure S2 because this improves the dynamic behaviour of the bridge. The results reveal that the pylon acts like a dynamic leverage arm magnifying the vertical response of the deck. Better results are obtained from performing structural-optimization and determination of control procedure simultaneously rather than separately.